Apigenin Suppresses Insulin-like Growth Factor I Receptor Signaling in Human Prostate Cancer: An In Vitro and In Vivo Study - Shukla, Sanjeev (2009)
Deregulation of insulin-like growth factor (IGF)-I/IGF-IR signaling has been implicated in the development and progression of prostate cancer. Agents that can suppress the mitogenic activity of the IGF/IGF-IR growth axis may be of preventive or therapeutic value. We have previously demonstrated that apigenin, a plant flavone, modulates IGF signaling through upregulation of IGFBP-3. In this study, we investigated the mechanism(s) of apigenin action on the IGF/IGF-IR signaling pathway. Exposure of human prostate cancer DU145 cells to apigenin markedly reduced IGF-I-stimulated cell proliferation and induced apoptosis. Apigenin inhibited IGF-I-induced activation of IGF-IR and Akt in DU145 cells. Similar growth inhibitory and apoptotic responses were observed in PC-3 cells, which constitutively over-express this pathway. This effect of apigenin appears to be due partially to reduced autophosphorylation of IGF-IR. Inhibition of p-Akt by apigenin resulted in decreased phosphorylation of GSK-3β along with decreased expression of cyclin D1 and increased expression of p27/kip1. In vivo administration of apigenin to PC-3 tumor xenografts inhibited tumor growth, resulted in IGF-IR inactivation and dephosphorylation of Akt and its downstream signaling. These results suggest that inhibition of cell proliferation and induction of apoptosis by apigenin are mediated, at least in part, by its ability to inhibit IGF/IGF-IR signaling and the PI3K/Akt pathway.